2011
DOI: 10.1111/j.1863-2378.2010.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation of Methicillin‐Resistant Staphylococcus aureus in Piglets

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as an important public health concern and pigs have been implicated in human infections. Cross-sectional studies have demonstrated that MRSA can be commonly found in pigs internationally, but little is known about age-related changes in MRSA colonization. This study evaluated MRSA colonization in piglets in a longitudinal manner. Serial nasal swabs were collected from piglets born to 10 healthy sows. The prevalence of MRSA colonization on days 1, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 20 publications
7
59
0
Order By: Relevance
“…While our findings indicate that CTX-M carriage decreases significantly after weaning, a similar longitudinal study (22) in pig farms in Denmark and the Netherlands showed a significant increase in the prevalence of LA-MRSA-positive animals after weaning. A similar trend was observed in another study from Canada (23). It remains unclear how the three pigs in farm C suddenly became CTX-M-positive carriers in the weaning section and negative again as finishers, while all other pigs included in the farm remained negative throughout the study.…”
Section: Discussionsupporting
confidence: 61%
“…While our findings indicate that CTX-M carriage decreases significantly after weaning, a similar longitudinal study (22) in pig farms in Denmark and the Netherlands showed a significant increase in the prevalence of LA-MRSA-positive animals after weaning. A similar trend was observed in another study from Canada (23). It remains unclear how the three pigs in farm C suddenly became CTX-M-positive carriers in the weaning section and negative again as finishers, while all other pigs included in the farm remained negative throughout the study.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, newborn piglets on breeding farms stay with the sow for at least 3 weeks. During this time, the opportunities to be colonized with MRSA via contact with the MRSA-positive sow or environment, or perhaps, via airborne contamination are frequent (28). Consequently, the piglets arrive at the weaner to grower farm or, later, at the fattening farm already colonized with MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Although ST398 is identified commonly in pigs and farming environments in North America [73,[92][93][94][125][126][127][128][129][130][131][132][133], there appears to be a greater diversity of molecular types found on North American farms compared with those in Europe, where ST398 remains the dominant or sole strain of MRSA identified. One study in Michigan found no ST398 present in the pigs sampled [134], whereas the bulk of studies have found a mix of Bhuman^types (such as ST8 and ST5) in conjunction with ST398.…”
Section: Evolution Of La-mrsa In North Americamentioning
confidence: 99%